Changes in oxygen saturation and the retinal nerve fibre layer in patients with optic neuritis associated with multiple sclerosis in a 6-month follow-up - Svrčinová, Tereza; Hok, Pavel; Šínová, Irena; Dorňák, Tomáš; Král, Michal; Hübnerová, Petra; Mareš, Jan; Kaňovský, Petr; Šín, Martin (Acta ophthalmologica, 2020)
PURPOSE: Optic neuritis (ON) is an inflammatory demyelinating disorder of the optic nerve, which can be the first manifestation of multiple sclerosis (MS). The main goal was to assess changes in the retinal nerve fibre layer (RNFL) and in retinal oxygen saturation [arterial (AS), venous (VS) and arterio-venous (A-V) difference] in the affected and unaffected eye. METHODS: Fifty patients with ON due to MS within 3 months of onset of symptoms were enrolled (17 males, mean age 35.3). All patients were examined at baseline (V1) and after 6 months (V2) using optical coherence tomography (OCT) to get RNFL values; automatic retinal oximetry to obtain saturation values; and ultrasound to exclude arterial stenosis, and orbital colour Doppler imaging was performed in the ophthalmic artery. RESULTS: At V1, AS was significantly increased in affected eye compared to unaffected eye (99.5% versus 98.0%, p = 0.03). Significant decrease in A-V difference from baseline was detected in both eyes for ON eye: 32.0% versus 29.0%, p = 0.004; for fellow eye: 31.4% versus 30.0%, p = 0.04. We did not observe any changes in retinal vessel diameter. There were no changes observed in blood flow in ophthalmic artery. At V1, there were no significant differences in RNFL, and significant loss of RNFL was confirmed in the affected eye at V2 (95 μm versus 86 μm, p = 0.0002) and in comparison with the fellow eye (86 μm versus 94 μm, p = 0.0002). There were no correlations between RNFL and saturation values at V1, although at V2, there was a negative correlation between the RNFL and AS (Spearman's rho = -0.480, p = 0.003) and between the RNFL and VS (rho = -0.620, p = 0.00007). CONCLUSION: Retinal oximetry is altered in both eyes in MS patients with unilateral ON. During the course of the disease, the retinal oxygen consumption decreases to a different degree in each eye and this change is not completely followed by changes in the RNFL thickness, suggesting either sub-clinical ON or systemic effects in the clinically unaffected eye. Since this is the first and initial longitudinal evaluation of the saturation changes in MS patients, the clinical value of these findings needs to be deeper evaluated in the future studies.
Keywords: Retinal Ganglion Cells; Humans; optical coherence tomography; lidé středního věku; Multiple Sclerosis; Oxygen Consumption; optic neuritis; retinální gangliové buňky; Optic Neuritis; Female; mladý dospělý; dospělí; optická koherentní tomografie; lidé; oxymetrie; časové faktory; zánět zrakového nervu; nervová vlákna; Adult; kyslík; Oxygen; Follow-Up Studies; ženské pohlaví; Optic Nerve; roztroušená skleróza; Male; multiple sclerosis; Middle Aged; nervus opticus; spotřeba kyslíku; Young Adult; Nerve Fibers; Tomography, Optical Coherence; Oximetry; mužské pohlaví; prospektivní studie; Time Factors; následné studie; oximetry; Prospective Studies